Tau Phosphorylation and Aggregation in the Developing Human Brain. Issue 10 (23rd July 2019) - Hefti, Marco M; Kim, SoongHo; Bell, Aaron J; Betters, Ryan K; Fiock, Kimberly L; Iida, Megan A; Smalley, Martin E; Farrell, Kurt; Fowkes, Mary E; Crary, John F
Abstract: Tau hyperphosphorylation, mostly at serine (Ser) or threonine (Thr) residues, plays a key role in the pathogenesis of Alzheimer disease (AD) and other tauopathies. Rodent studies show similar hyperphosphorylation in the developing brain, which may be involved in regulating axonal growth and plasticity, but detailed human studies are lacking. Here, we examine tau phosphorylation by immunohistochemistry and immunoblotting in human fetal and adult autopsy brain tissue. Of the 20 cases with sufficient tissue preservation, 18 (90%) showed positive staining for S214 (pSer214), with the majority also positive for CP13 (pSer202), and PHF-1 (pSer396/pSer404). AT8 (pSer202/pThr205) and RZ3 (pThr231) were largely negative while PG5 (pSer409) was negative in all cases. Immunoblotting showed tau monomers with a similar staining pattern. We also observed phospho-tau aggregates in the fetal molecular layer, staining positively for S214, CP13, and PHF1 and negative for thioflavin S. These corresponded to high-molecular weight (∼150 kD) bands seen on Western blots probed with S214, PHF1, and PG5. We therefore conclude that fetal phosphorylation overlaps with AD in some residues, while others (e.g. T231, S409) appear to be unique to AD, and that tau is capable of forming nontoxic aggregates in the developing brain. These findings suggest that the fetal brain is resilient to formation of toxic aggregates, the mechanism for which may yield insights into the pathogenesis of tau aggregation and toxicity in the aging brain.